Blood in their eyes : the Elaine Massacre of 1919 - Stockley, Grif (The University of Arkansas Press, 2020)
"The second edition of the authoritative text on the Elaine Massacre which took place in Elaine, Arkansas in 1919. With contributions by fellow historians Brian K. Mitchell and Guy Lancaster, this second edition of Blood in Their Eyes draws from recently discovered sources to explore in greater detail the actions of the mob and the lives of those who survived the massacre"-- Provided by publisher.
Keywords: United States. -- Army -- Civic action -- History -- 20th century.; United States. -- Army; Riots -- Arkansas -- Elaine -- History -- 20th century.; Massacres -- Arkansas -- Elaine -- History -- 20th century.; Sharecroppers -- Arkansas -- Phillips County -- Social conditions -- 20th century.; African Americans -- Arkansas -- Phillips County -- Social conditions -- 20th century.; African Americans -- Legal status, laws, etc. -- Arkansas -- Phillips County -- History -- 20th century.; Trials (Murder) -- Arkansas -- Phillips County -- History -- 20th century.; Elaine Massacre, Elaine, Ark., 1919.; Phillips County (Ark.) -- Race relations.; Elaine (Ark.) -- Race relations.; Camp Pike (Ark.) -- History -- 20th century.; Métayers -- Arkansas -- Phillips -- Conditions sociales -- 20e siècle.; Noirs américains -- Arkansas -- Phillips -- Conditions sociales -- 20e siècle.; Procès (Meurtre) -- Arkansas -- Phillips -- Histoire -- 20e siècle.; SOCIAL SCIENCE / General; African Americans -- Legal status, laws, etc.; African Americans -- Social conditions; Armed Forces -- Civic action; Massacres; Race relations; Riots; Trials (Murder); Arkansas -- Camp Joseph T. Robinson; Arkansas -- Elaine; Arkansas -- Phillips County; Legal status.; 1900-1999; Electronic books.; History